LI-FI Become IOE: A Novel Architecture for LED - Draz, Umar; Ali, Tariq; Yasin, Sana; Shaf, Ahmad; Shakoor, Ayesha; Waqas, Umair (EAI Endorsed Transactions on Scalable Information Systems, 2018)
Abstract. Nowadays LI-FI attracts the intention of the whole world. With in no time, the idea of LI-FI spread in the ﬁeld of wireless communication technology. The working of LI-FI is purely based upon visible light communication in the form of LED. Due to VLC and LED LI-FI not only become an important part of the internet of things (IOT) but also internet of everything (IOE). LI-FI deal with a large amount of data rate, which is in the range of several Mbs to Gbs. Diﬀerent parameters are aﬀected by the performance of data rate. The proper arrangement of LED play part and parcel role in this new technology so there needs to investigate the novel architecture and ﬂow control protocol in LI-FI system. The dimension of LED and the position of LED lead this technology towards high data rate. So, this paper presents the actual technique and novel architecture that tells us how to increase the data rate in front of diﬀerent parameters.